An alternative approach for the analysis and forecasting of economic series : the state space modelling - Maurin, Alain ([Caribbean Centre for Money & Finance] [St. Augustine]TT, 1996)
Examines what could be the contributions of the state space representation to modelize and forecast the evolution of Caribbean economic variables.